Stagflationary pressures in the condition of global economic shocks - Pejčić Jovica; Sekulić Aleksandar; Glavaški Olgica (Anali Ekonomskog fakulteta u Subotici)
This paper analyses the key macroeconomic repercussions of the global pandemic and geopolitical crisis in terms of growing recessionary and inflationary pressures, and finally, the potential occurrence of stagflation. The subject of the econometric analysis is aimed at seeing how global energy price movements, unemployment rates, interest rates and money supply affect: (1) real gross domestic product; and 2) the movement of the inflation rate in the sample of 18 countries (EU-15, USA, Norway and Switzerland) in the period 2020q1-2023q1. Using Panel-corrected standard errors method (PCSE), two panel models are estimated in which the dependent variables are: (a) the real gross domestic product, showing potential recessionary pressures, and (b) the inflation rate, determining inflationary pressures. Results indicated that in the observed period, inflationary and recessionary pressures existed in the sample of 18 developed economies, as well as that these pressures can be characterized as the phenomenon of stagflation. The most profound impact on recessionary circumstances was caused by the rise in global energy prices in the second and third quarters of 2022, which can be considered as an exogenous shock and trigger of recessionary pressures, while inflationary pressures are dominantly determined by global oil price growth during the analysed period.